2013
DOI: 10.7150/ijms.6294
|View full text |Cite
|
Sign up to set email alerts
|

An Anti-Infection Tissue-Engineered Construct Delivering Vancomycin: its Evaluation in a Goat Model of Femur Defect

Abstract: A tissue-engineered construct (TEC) has previously been used for treating bone defects due to its strong osteogenic capability. However, transplantation of a TEC involves an open surgery that can cause infection. To overcome the potential risk of infection after TEC transplantation, we designed a system for the controlled release of antibiotics using fibrin gel-coated vancomycin alginate beads (FG-Vanco-AB) that can supply sustained antibiotics at the graft site. A TEC with FG-Vanco-AB was transplanted into cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Using tissue engineering, Xing et al 81 created a biodegradable composite of vancomycin alginate beads and fibrin gel scaffolds to treat chronic osteomyelitis in a rabbit model, promoting positive results. Chang et al 82 confirmed these results in a goat model, reporting a minimum inhibitory concentration (MIC) of vancomycin against S. aureus in a bone defect for at least 28 days.…”
Section: Tissue Engineeringmentioning
confidence: 75%
“…Using tissue engineering, Xing et al 81 created a biodegradable composite of vancomycin alginate beads and fibrin gel scaffolds to treat chronic osteomyelitis in a rabbit model, promoting positive results. Chang et al 82 confirmed these results in a goat model, reporting a minimum inhibitory concentration (MIC) of vancomycin against S. aureus in a bone defect for at least 28 days.…”
Section: Tissue Engineeringmentioning
confidence: 75%
“…182 In their future in vivo study, they showed that inclusion of vancomycin alginate beads/ fibrin in a DBM exhibited no negative impact on the process of osteogenesis and wound healing in the femoral defects of goats. 183 In addition, they successfully treated chronic osteomyelitis of rabbit tibia by a vancomycin alginate bead/ BMSCs/fibrin gel delivery system.…”
mentioning
confidence: 99%
“…The final published version may differ from this proof. 14 Currently, no satisfactory results have been reported regarding the clinical application of large bone grafts modified with SAPs. One reason is that the reconstruction of large bone defects remains a challenge (33).…”
Section: Discussionmentioning
confidence: 99%
“…Goat mesenchymal stem cells (gMSCs) were harvested as previously described (14). Sixty to eighty microliters of cell suspension was instilled slowly onto one side of the post-enriched SAP/DBM or DBM.…”
Section: Cell Distribution After Osteogenic Differentiationmentioning
confidence: 99%